A schizophrenia study based on multi-frequency dynamic functional connectivity analysis of fMRI - Shi, Yuhu; Shen, Zehao; Zeng, Weiming; Luo, Sizhe; Zhou, Lili; Wang, Nizhuan (Frontiers in Human Neuroscience, 2023)
At present, fMRI studies mainly focus on the entire low-frequency band (0. 01–0.08 Hz). However, the neuronal activity is dynamic, and different frequency bands may contain different information. Therefore, a novel multi-frequency-based dynamic functional connectivity (dFC) analysis method was proposed in this study, which was then applied to a schizophrenia study. First, three frequency bands (Conventional: 0.01–0.08 Hz, Slow-5: 0.0111–0.0302 Hz, and Slow-4: 0.0302–0.0820 Hz) were obtained using Fast Fourier Transform. Next, the fractional amplitude of low-frequency fluctuations was used to identify abnormal regions of interest (ROIs) of schizophrenia, and dFC among these abnormal ROIs was implemented by the sliding time window method at four window-widths. Finally, recursive feature elimination was employed to select features, and the support vector machine was applied for the classification of patients with schizophrenia and healthy controls. The experimental results showed that the proposed multi-frequency method (Combined: Slow-5 and Slow-4) had a better classification performance compared with the conventional method at shorter sliding window-widths. In conclusion, our results revealed that the dFCs among the abnormal ROIs varied at different frequency bands and the efficiency of combining multiple features from different frequency bands can improve classification performance. Therefore, it would be a promising approach for identifying brain alterations in schizophrenia.